New teaching methods used in the study of the discipline Intercultural communication and translation problems (Journal of Oriental Studies, 2016)
In this article the urgency of using сompetenсе- oriented technology used in teaching the discipline "Intercultural communication and translation problems." The author presents his own method of teaching this distsiliny and makes recommendations for successful implementation сompetenсе- oriented technology in the educational process.
Keywords: intercultural communication; idioms; innovative technology; focus; competence method